Human Placental Hofbauer Cells Maintain an Anti-inflammatory M2 Phenotype despite the Presence of Gestational Diabetes Mellitus - Schliefsteiner, Carolin; Peinhaupt, Miriam; Kopp, Susanne; Lögl, Jelena; Lang-Olip, Ingrid; Hiden, Ursula; Heinemann, Akos; Desoye, Gernot; Wadsack, Christian (Frontiers in Immunology, 2017)
Background: Hofbauer cells (HBCs) are macrophages of the feto-placental unit. Despite the general view that these cells have an anti-inflammatory M2 phenotype, recent studies have claimed that pregnancy pathologies – e.g. gestational diabetes (GDM) – cause a switch from an M2 to an M1 pro-inflammatory phenotype in HBCs. The pilot-study presented here challenges this claim, showing that HBCs maintain anti-inflammatory properties in spite of the hyperglycemic, low-grade inflammatory environment of GDM. Methods: HBCs were isolated from placentae of healthy women (N=5) and women with GDM (N=6) diagnosed in the second trimester. FACS was used to measure surface markers associated with either M1 or M2 phenotype on the cells. Additionally, placental tissue sections were subjected to immune histochemical imaging to assess the phenotype within the tissue context. Supernatant from control and GDM HBCs was collected at defined time points and used in a Multiplex ELISA-on-beads approach to assess secretion of cytokines, chemokines and growth factors. The effect of HBC cell culture supernatant on placental endothelial activation was investigated. Results: FACS and immune staining showed that indeed, M2 markers such as CD206 and CD209 are increased in HBCs isolated from GDM placentae. Also, the M1 marker CD86 was increased, but only by trend. Secretion of numerous cytokines, chemokines and growth factors was not changed; pro-inflammatory IL-1β and IL-6 release form GDM HBC was increased but not significant. Exposure to GDM HBC supernatant did not induce cell adhesion molecules (VCAM-1, Selectins, VE-Cadherin) in placental endothelial cells compared to supernatant from control HBCs, an induction of ICAM-1 was observed however. Conclusion: Our study – although performed in a small set of patients - shows that placental macrophages maintain their anti-inflammatory, tissue-remodeling M2 phenotype even in pregnancies affected by gestational diabetes. This consistent phenotype might be important for propagation of maternal tolerance towards the fetus and for protection of the fetus from a low-grade inflammatory environment. Results: FACS and immune staining showed that indeed, M2 markers such as CD206 and CD209 are increased in HBCs isolated from GDM placentae. Also, the M1 marker CD86 was increased, but only by trend. Secretion of numerous cytokines, chemokines